Carbonate-associated sulfate isotope signatures in marine mollusk shells - Shanggui Gong; Yongbo Peng; Laurie C. Anderson; Annette Summers Engel; Huiming Bao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Financial viability and carbon intensity of hydrothermal waste valorization systems for bio-based asphalt binder - Ali Ahmad; Harshal D. Kawale; Sabrina Summers; Barbara Camila Bogarin Cantero; Cody M. Allen; Ramez M. Hajj; Paul C. Davidson; Yuanhui Zhang; Yalin Li (Chemical Engineering Journal, 2026)

Advancing the Implementation of Coastal Restoration in Louisiana Through a Co-production of Science Framework - Jacob M. Oster; Jessica R. Henkel; Alyssa Dausman; Eva D. Windhoffer; Bingqing Liu; Melissa M. Baustian; Denise Reed; Summer Langlois; David C. Lindquist (Estuaries and Coasts, 2025)
Coastal Louisiana faces complex challenges from the compounding effects of coastal land loss and climate change. The State of Louisiana’s Coastal Protection and Restoration Authority (CPRA) and the RESTORE Act Center of Excellence for Louisiana (LA-COE) have adopted a co-production of science framework to help ensure that scientific research funded through the LA-COE supports the research needs of CPRA and the Louisiana Coastal Master Plan (CMP), a large-scale coastal restoration plan that outlines activities needed to restore and protect Louisiana’s coast. In this paper, we describe the co-production of science framework established between the LA-COE, CPRA, and research projects funded by the LA-COE. Through an iterative process, the Louisiana CMP is revised every 6 years with improved model and scientific information. The LA-COE leverages the cyclical nature of the CMP by working with CPRA to identify research needs for each Request for Proposals solicited by the LA-COE. The LA-COE proposal review process is structured to include anonymous CPRA review of projects to promote the production of actionable science, and once funded, multiple mechanisms are in place to support collaboration between researchers and CPRA staff. We highlight these mechanisms and provide examples of four LA-COE-funded projects where co-produced science is being used by CPRA to inform the CMP and its implementation. Finally, we discuss challenges of co-production within the confines of funding requirements and review restrictions, highlighting how the LA-COE continues to adapt to navigate these challenges and enhance the implementation of co-production throughout the research funding lifecycle.

Broad‐scale climate patterns combined with local flow and turbidity disturbances structure the seasonality of gross primary production in an aridland river - Betsy M. Summers; Robert O. Hall; Justin K. Reale; Eric Joseph; Mark C. Stone; David J. Van Horn (Limnology and Oceanography, 2025)
Both local and global climate phenomena shape the hydrologic regimes of watersheds. For aridland rivers in the southwestern United States, peak flows occur during two distinct periods: spring snowmelt and summer monsoons. Although discharge ( Q ) is a primary driver of variation in the production and consumption of instream organic matter, or stream metabolism, few connection have been made regarding how climate impacts ecosystem processes through changes in flow and related disturbances. We considered how variation in disturbance variables, specifically Q and associated changes in turbidity, affected gross primary production during spring snowmelt and summer monsoons in the Rio Grande. Nine years of continuous environmental data ( Q , turbidity, light) and climate indices (i.e., El Niño‐Southern Oscillation and Monsoon Index) were used to explain the variation in gross primary production estimates. We found that relationships were sensitive to the timescale of disturbance: at the seasonal scale, high snowmelt Q decreased spring mean gross primary production, while at the daily scale, high turbidity, and to a lesser extent Q , reduced gross primary production during summer. Also, mean Q and turbidity disturbances were uncoupled in spring and inversely related in summer. We conclude that long‐term datasets are essential to uncover emergent relationships between broad‐scale climate patterns and ecosystem processes and are necessary to better understand how hydroclimatic variability drives ecosystem processes at varying time scales in rivers across Earth.

Near-infrared induced photothermal lateral-flow immunoassay utilizing plasmonics-active gold nanostars - Supriya Atta; Yuanhao Zhao; Sebastian Sanchez; Sabina V. Yampolsky; Vanessa K. Berner; Marcellene A. Gates-Hollingsworth; Jasmine Pramila Devadhasan; Alexander Jarrett Summers; Jian Gu; Douglas C. Montgomery; David P. AuCoin; Frederic Zenhausern; et al. (Analytica Chimica Acta, 2025)

Micropuncture and granular hydrogel scaffolds to surgically bioengineer a perfusable and stably patterned microvasculature - Jessica C. El-Mallah; Zaman Ataie; Summer N. Horchler; Mary E. Landmesser; Mohammad Hossein Asgardoon; Olivia Waldron; Arian Jaberi; Alexander Kedzierski; Mingjie Sun; Amir Sheikhi; Dino J. Ravnic (Angiogenesis, 2025)
Vascularization of implanted biomaterials is critical to reconstructive surgery and tissue engineering. Ultimately, the goal is to promote a rapidly perfusable hierarchical microvasculature that persists with time and can meet underlying tissue needs. We have previously shown that using a microsurgical technique, termed micropuncture (MP), in combination with porous granular hydrogel scaffolds (GHS) fabricated via interlinking hydrogel microparticles (microgels) results in a rapidly perfusable patterned microvasculature. However, whether this engineered microvasculature remains stable at longer time points remains unknown. Here, we combine MP with GHS and compare overall microvascular architecture and phenotype along with the evolving cellular landscape over a 28 day period. We demonstrate perfusable patterned microvascular stability in our MP + GHS model that occurs alongside a sustained rise in endothelial cell and macrophage recruitment. Specifically, MP yields a significant rise in M2 macrophages between the 7 and 28 day time points, suggesting ongoing microvascular remodeling, even in the presence of early pericyte stabilization. With time, the GHS microvasculature acquires a relatively equivalent arterial and venous morphology, as assessed through Ephrin-B2 and EphB4 quantification. Finally, angiography at 28 days shows that MP + GHS is associated with more perfusable microvascular loops when compared with MP + Bulk (nonporous) scaffolds. Hence, our surgically bioengineered microvasculature offers a unique opportunity to sustainably and precisely control biomaterial vascularization and ultimately advance the fields of reconstructive surgery and tissue engineering.

Cryptic anatomical adaptive peak shifts and transitions along the body elongation continuum in zoarcoid fishes - Summer E. Duba; David C. Collar (Zoology, 2025)

Mapping barriers to food, energy, and water systems equity in the United States - Haleigh N. Summers; Tiffanie F. Stone; Loulou C. Dickey; Chris R. Rehmann; Emily K. Zimmerman; John C. Tyndall; Lu Liu (Environmental Science & Policy, 2024)

Development of a generalized pseudo-probabilistic approach for characterizing ecological conditions in estuaries using secondary data - Linda C. Harwell; Courtney A. McMillion; Andrea M. Lamper; J. Kevin Summers (Environmental Monitoring and Assessment, 2024)
Under the best circumstances, achieving or sustaining optimum ecological conditions in estuaries is challenging. Persistent information gaps in estuarine data make it difficult to differentiate natural variability from potential regime shifts. Long-term monitoring is critical for tracking ecological change over time. In the United States (US), many resource management programs are working at maximum capacity to address existing state and federal water quality mandates (e.g., pollutant load limits, climate impact mitigation, and fisheries management) and have little room to expand routine sampling efforts to conduct periodic ecological baseline assessments, especially at state and local scales. Alternative design, monitoring, and assessment approaches are needed to help offset the burden of addressing additional data needs to increase understanding about estuarine system resilience when existing monitoring data are sparse or spatially limited. Research presented here offers a pseudo-probabilistic approach that allows for the use of found or secondary data, such as data on hand and other acquired data, to generate statistically robust characterizations of ecological conditions in estuaries. Our approach uses a generalized pseudo-probabilistic framework to synthesize data from different contributors to inform probabilistic-like baseline assessments. The methodology relies on simple geospatial techniques and existing tools (R package functions) developed for the US Environmental Protection Agency to support ecological monitoring and assessment programs like the National Coastal Condition Assessment. Using secondary estuarine water quality data collected in the Northwest Florida (US) estuaries, demonstrations suggest that the pseudo-probabilistic approach produces estuarine condition assessment results with reasonable statistical confidence, improved spatial representativeness, and value-added information. While the pseudo-probabilistic framework is not a substitute for fully evolved monitoring, it offers a scalable alternative to bridge the gap between limitations in resource management capability and optimal monitoring strategies to track ecological baselines in estuaries over time.

PMAxx-RT-qPCR to Determine Human Norovirus Inactivation Following High-Pressure Processing of Oysters - Andri Taruna Rachmadi; Pradip Gyawali; Graeme Summers; Anower Jabed; Graham C. Fletcher; Joanne Hewitt (Food and Environmental Virology, 2024)

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Examination of the potential of refrigerated seawater to improve live transport of the mussel Perna canaliculus: Physiological responses, meat quality and safety implications under different chilled storage conditions - Nicholas P.L. Tuckey; Belinda A. Timms; Graham C. Fletcher; Graeme Summers; Natalí J. Delorme; Jessica A. Ericson; Norman L.C. Ragg; Poppy Miller; Reginald Wibisono; Roland Taylor; Serean L. Adams; Leonardo N. Zamora (Aquaculture, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Soil CO2 in organic and no-till agroecosystems - Summer R.A. Lockhart; C. Kent Keller; R. David Evans; Lynne A. Carpenter-Boggs; David R. Huggins (Agriculture, Ecosystems & Environment, 2023)

Perfluoroalkyl substances exposure in firefighters: Sources and implications - Paul E. Rosenfeld; Kenneth R. Spaeth; Linda L. Remy; Vera Byers; Stuart A. Muerth; Ryan C. Hallman; Jasmine Summers-Evans; Sofia Barker (Environmental Research, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Female preference for super-sized male ornaments and its implications for the evolution of ornament allometry - Thomas C. Summers; Terry J. Ord (Evolutionary Ecology, 2022)
It has been argued that disproportionately larger ornaments in bigger males—positive allometry—is the outcome of sexual selection operating on the size of condition dependent traits. We reviewed the literature and found a general lack of empirical testing of the assumed link between female preferences for large ornaments and a pattern of positive allometry in male ornamentation. We subsequently conducted a manipulative experiment by leveraging the unusual terrestrial fish, Alticus sp. cf. simplicirrus , on the island of Rarotonga. Males in this species present a prominent head crest to females during courtship, and the size of this head crest in the genus more broadly exhibits the classic pattern of positive allometry. We created realistic male models standardized in body size but differing in head crest size based on the most extreme allometric scaling recorded for the genus. This included a crest size well outside the observed range for the study population (super-sized). The stimuli were presented to free-living females in a manner that mimicked the spatial distribution of courting males. Females directed greater attention to the male stimulus that exhibited the super-sized crest, with little difference in attention direct to other size treatments. These data appear to be the only experimental evidence from the wild of a female preference function that has been implicitly assumed to drive selection that results in the evolution of positive allometry in male ornamentation.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Development of metabolic inflammation during pre-hibernation fattening in 13-lined ground squirrels (Ictidomys tridecemlineatus) - Michelle M. Sonsalla; Santidra L. Love; Laurana J. Hoh; Lauren N. Summers; Hannah M. Follett; Aminata Bojang; Khrystyne N. Duddleston; Courtney C. Kurtz (Journal of Comparative Physiology B, 2021)

Deep‐time convergent evolution in animal communication presented by shared adaptations for coping with noise in lizards and other animals - Terry J. Ord; Danielle A. Klomp; Thomas C. Summers; Arvin Diesmos; Norhayati Ahmad; Indraneil Das (Ecology Letters, 2021)
Convergence in communication appears rare compared with other forms of adaptation. This is puzzling, given communication is acutely dependent on the environment and expected to converge in form when animals communicate in similar habitats. We uncover deep‐time convergence in territorial communication between two groups of tropical lizards separated by over 140 million years of evolution: the Southeast Asian Draco and Caribbean Anolis . These groups have repeatedly converged in multiple aspects of display along common environmental gradients. Robot playbacks to free‐ranging lizards confirmed that the most prominent convergence in display is adaptive, as it improves signal detection. We then provide evidence from a sample of the literature to further show that convergent adaptation among highly divergent animal groups is almost certainly widespread in nature. Signal evolution is therefore curbed towards the same set of adaptive solutions, especially when animals are challenged with the problem of communicating effectively in noisy environments.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Diatom assemblage changes in shallow lakes of the Athabasca Oil Sands Region are not tracking aerially deposited contaminants - Nell Libera; Jamie C. Summers; Kathleen M. Rühland; Joshua Kurek; John P. Smol (Journal of Paleolimnology, 2020)

Land use drives nitrous oxide dynamics in estuaries on regional and global scales - Michael J. Reading; Douglas R. Tait; Damien T. Maher; Luke C. Jeffrey; Arun Looman; Ceylena Holloway; Haile A. Shishaye; Summer Barron; Isaac R. Santos (Limnology and Oceanography, 2020)
Urban and agricultural development of coastal catchments is known to increase dissolved nitrogen inputs into estuaries; however, much less is known about how land use influences the production of the powerful greenhouse gas nitrous oxide (N 2 O). Here, we assess dissolved N 2 O dynamics in four nearby estuaries across a regional land use gradient and summarize the literature to put the observations into global perspective. During summer dry conditions, N 2 O saturation ranged from 131.4% ± 45.0% in the most pristine system (28% modified) to 198.6% ± 52.3% within the most modified urban system (91% modified). The N 2 O saturation in the wetter winter campaign was higher and more variable than the summer dry campaign (range 84.7–677.7%) likely due to direct transport of N 2 O into the estuaries from catchment runoff and/or produced through denitrification fueled by high nitrate inputs. During both seasons, N 2 O was lowest in areas adjacent to fringing mangroves and highest in upstream fresh/saltwater mixing areas. Coupling our results with previously published N 2 O data from 50 estuarine systems worldwide revealed that estuarine N 2 O increases concomitantly with catchment modification, dissolved inorganic nitrogen availability, and decreasing oxygen concentrations. Based on these results, a 1% increase in anthropogenic modification to global catchments (i.e., agricultural development and/or urbanization) may increase estuarine N 2 O saturation by 2.6% ± 1.2%. These findings indicate that future estuarine N 2 O emissions are likely to increase as anthropogenic modification of coastal catchments intensifies.

Knowledge, attitudes and practices of health care professionals towards adverse drug reaction reporting in public sector primary health care facilities in a South African district - H. M. Haines; J. C. Meyer; R. S. Summers; B. B. Godman (European Journal of Clinical Pharmacology, 2020)
Purpose Adverse drug reactions (ADRs) have an appreciable impact on patients’ health. Little is known however about ADR reporting in ambulatory care environments especially in low- and middle-income countries. Consequently, our aim was to determine knowledge, attitudes and practices (KAP) among health care professionals (HCPs) towards ADR reporting in primary health care (PHC) facilities in South Africa. The findings will be used to direct future activities. Methods Descriptive, cross-sectional design using quantitative methodology among 8 public sector community health care centres and 40 PHC clinics in the Tshwane Health District, Gauteng Province. A self-administered questionnaire was distributed to 218 HCPs, including all key groups. Results A total of 200 responses were received (91.7%). Although an appropriate attitude towards ADR reporting existed, the actual frequency of ADR reporting was low (16.0%). Of the respondents, 60.5% did not know how to report, where to report or when to report an ADR and 51.5% said the level of their clinical knowledge made it difficult to decide whether or not an ADR had occurred. Over 97.5% stated they should be reporting ADRs with 89% feeling that ADR reporting is a professional obligation and over 70% that ADR reporting should be compulsory. When results were combined, the overall mean score in terms of positive or preferred practices for ADR reporting was 24.6% with pharmacists having the highest scores. Conclusion Under-reporting of ADRs with gaps in KAP was evident. There is a serious and urgent need for education and training of HCPs on ADR reporting in South Africa.

Ketamine induces immediate and delayed alterations of OCD-like behavior - Summer L. Thompson; Amanda C. Welch; Julia Iourinets; Stephanie C. Dulawa (Psychopharmacology, 2020)

A diatom-based paleolimnological survey of environmental changes since ~ 1850 in 18 shallow lakes of the Athabasca Oil Sands Region, Canada - Jamie C. Summers; Kathleen M. Rühland; Joshua Kurek; John P. Smol (Journal of Paleolimnology, 2019)

Trimethylamine oxide content and spoilage potential of New Zealand commercial fish species - G. Summers; R. D. Wibisono; D. I. Hedderley; G. C. Fletcher (New Zealand Journal of Marine and Freshwater Research, 2017)
Breakdown of trimethylamine oxide (TMAO) during post‐harvest storage contributes significantly to loss of seafood quality. We surveyed 51 New Zealand commercial fish species and determined white muscle tissue concentrations of TMAO and the TMAO‐derived spoilage indices: trimethylamine nitrogen (TMA‐N) and total volatile basic nitrogen (TVB‐N). There were significant differences in the TMAO concentrations between fish of various genus and species. Values ranged between 8 and 789 mg/100 g for ray‐finned fishes (Actinopterygii), and 262 and 789 mg/100 g for cartilaginous fishes. The distribution of TMAO was similar to that of Northern Hemisphere fish species. Deep water species had the highest concentrations of TMAO. Seasonal effects in tarakihi ( Nemadactylus macropterus ) and red gurnard ( Chelidonichthys kumu ) were studied and TMAO declined significantly over the summer months. TMA‐N was typically below 2 mg/100 g and TVB‐N concentrations did not exceed the limits set by the European Community (EC) Commission Regulation No. 1022/2008.

Clinically effective OCD treatment prevents 5-HT1B receptor-induced repetitive behavior and striatal activation - Emily V. Ho; Summer L. Thompson; William R. Katzka; Mitra F. Sharifi; James A. Knowles; Stephanie C. Dulawa (Psychopharmacology, 2016)

Lead and Cadmium in the Blood of Nine Species of Seabirds, Marion Island, South Africa - Carly F. Summers; William W. Bowerman; Nola Parsons; Wayne Y. Chao; William C. Bridges (Bulletin of Environmental Contamination and Toxicology, 2014)

Predator driven reproductive behavior in a tropical frog - C. Seabird McKeon; Kyle Summers (Evolutionary Ecology, 2013)

14-3-3s are potential biomarkers for HIV-related neurodegeneration - Diana Morales; Efthimios C. M. Skoulakis; Summer F. Acevedo (Journal of NeuroVirology, 2012)

Spatial Ecology of the Endangered Milne-Edwards’ Sifaka (Propithecus edwardsi): Do Logging and Season Affect Home Range and Daily Ranging Patterns? - Brian D. Gerber; Summer Arrigo-Nelson; Sarah M. Karpanty; Mary Kotschwar; Patricia C. Wright (International Journal of Primatology, 2012)

Tissue functions mediated by β3-adrenoceptors—findings and challenges - Martin C. Michel; Peter Ochodnicky; Roger J. Summers (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Feathers as bioindicators of PCB exposure in clapper rails - J. W. Summers; K. F. Gaines; N. Garvin; W. L. Stephens; J. C. Cumbee; G. L. Mills (Ecotoxicology, 2010)

Response of the hammerhead shark olfactory epithelium to amino acid stimuli - Timothy C. Tricas; Stephen M. Kajiura; Adam P. Summers (Journal of Comparative Physiology A, 2009)

Assessing coastal waters of American Samoa: territory-wide water quality data provide a critical “big-picture” view for this tropical archipelago - Guy T. DiDonato; Eva M. DiDonato; Lisa M. Smith; Linda C. Harwell; J. Kevin Summers (Environmental Monitoring and Assessment, 2009)

Accentuation of phosphorus limitation in Geranium dissectum by nitrogen: an ecological genomics study - SUSAN SUMMERS THAYER; SAMUEL B. ST CLAIR; CHRISTOPHER B. FIELD; SHAUNA C. SOMERVILLE (Global Change Biology, 2008)
Global climate change experiments have shown changes in productivity, phenology, species composition, and nutrient acquisition and availability; yet, the underlying mechanisms for these responses, especially in multi‐factorial experiments, are poorly understood. Altered nutrient availability is a major consequence of global change, directly due to anthropogenic nitrogen (N) deposition, and indirectly due to shifts in temperature and water availability. In the Jasper Ridge Global Change Experiment, microarrays were used to investigate the transcriptional responses of the dominant dicot, Geranium dissectum , to simulated N deposition. The transcript levels for several photosynthetic genes were elevated in plants exposed to elevated N, as has been reported previously, validating the use of microarrays under field conditions. A coordinated response of a suite of genes previously reported to be induced in response to phosphate (Pi) deficiency was observed, including genes for the glycolytic bypass pathway, which reduces ATP and Pi requirements for sugar degradation, suggesting that the plants were phosphorus (P) limited. Confirming this conclusion, foliar P levels in G. dissectum leaves were reduced to levels that are suboptimal for growth in plants grown in elevated N and elevated CO 2 plots. Thus, although plants commonly produce more biomass in response to elevated N in native grasslands, this growth response may be suboptimal due to a P limitation. Foliar P levels in plants from elevated CO 2 plots were also suboptimal for growth. However, genes indicative of Pi deficiency were not significantly expressed at higher levels. Transcript levels for genes involved in nitrate uptake and assimilation were unchanged by the elevated N deposition treatment, possibly due to the combined impacts of elevated N deposition and P limitation under field conditions. These observations highlight the complexity of the impact of global climate change factors in the field.

The Ecological Condition of Gulf of Mexico Resources from Perdido Key to Port St. Joe, Florida, USA: Part I. Coastal Beach Resources - Lisa M. Smith; Eva M. Didonato; Linda C. Harwell; Janet A. Nestlerode; J. Kevin Summers (Environmental Monitoring and Assessment, 2007)

The ecological condition of Gulf of Mexico resources from Perdido Key to Port St. Joe, Florida: Part II near-shelf coastal resources - Lisa M. Smith; James E. Harvey; Linda C. Harwell; J. Kevin Summers (Environmental Monitoring and Assessment, 2007)

The condition of coral reefs in South Florida (2000) using coral disease and bleaching as indicators - Deborah L. Santavy; J. Kevin Summers; Virginia D. Engle; Linda C. Harwell (Environmental Monitoring and Assessment, 2005)

Tyrosinase gene mutations in oculocutaneous albinism1 (OCA1): definition of the phenotype - Richard A. King; Jacy Pietsch; James P. Fryer; Sarah Savage; Marcia J. Brott; Isabelle Russell-Eggitt; C. Gail Summers; William S. Oetting (Human Genetics, 2003)

The Ecological Condition of South Florida Estuaries - J. M. Macauley; J. K. Summers; V. D. Engle; L. C. Harwell (Environmental Monitoring and Assessment, 2002)

The murine chaperonin 10 gene family contains an intronless, putative gene for early pregnancy factor, Cpn10-rs1 - Barbara H. Fletcher; A. Ian Cassady; Kim M. Summers; Alice C. Cavanagh (Mammalian Genome, 2001)

Canine distemper virus infection and encephalitis in javelinas (collared peccaries) - M. J. G. Appel; C. Reggiardo; B. A. Summers; S. Pearce-Kelling; C. J. Mare; T. H. Noon; R. E. Reed; J. N. Shively; C. rvell (Archives of Virology, 1991)

A coordinate relationship between theGALK and theTK1 genes of the Chinese hamster - Robert P. Wagner; Summers H. Cox; Robert C. Schoen (Biochemical Genetics, 1985)

A coordinate relationship between theGALK and theTK1 genes of the Chinese hamster - Robert P. Wagner; Summers H. Cox; Robert C. Schoen (Biochemical Genetics, 1985)

Interferon in cerebrospinal fluid - S. C. Tsai; B. A. Summers; M. J. G. Appel (Archives of Virology, 1982)

The effect of high yields on cost of production in Colorado - C. H. Metzger; T. H. Summers (American Journal of Potato Research, 1930)